Successful Treatment of Drug-Resistant Seizures Secondary to Ring 20 Mosaicism with Perampanel as an Add-On Antiepileptic Drug - Janet Ling; Wai Lan Yeung; Kam Lun Hon; Ivan F. M. Lo; Ho-Ming Luk; Cheuk Wing Fung; Alexander K. C. Leung (Case Reports in Pediatrics)
We report a girl with drug-resistant seizures, progressive behavioral changes, and cognitive decline. Investigations showed abnormal EEG with frequent high-voltage bifrontotemporal sharp and slow waves, especially during sleep. Seizures were difficult to control, despite the usage of various antiepileptic drugs. Perampanel as an add-on antiepileptic drug appeared efficacious. Due to the recognizable pattern of seizures and EEG findings, a karyotype study was performed which revealed 46 chromosomes with a ring 20 chromosome mosaicism. Ring 20 chromosome is associated with drug-resistant refractory seizures, cognitive decline, and behavioral problems. This case highlights the difficulty and challenge faced in managing drug-resistant refractory seizures associated with ring 20 chromosome. While ring 20 chromosome is often underdiagnosed, one should have a high index of awareness and suspicion of such rare epilepsy syndrome, so that an early diagnosis can be made.